2020
DOI: 10.1108/sjme-06-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

The role of customer personality in satisfaction, attitude-to-brand and loyalty in mobile services

Abstract: Purpose The purpose of this study is two-fold. First is to explore the role of some customer personality traits in explaining customer satisfaction in mobile services. Second is to explore the relationship between satisfaction and loyalty of mobile services customers, mediated by attitude-to-brand considering the fierce competition and the fast industry growth. Design/methodology/approach The study used a cross-sectional design and a survey of mobile service customers. For the empirical analysis, the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 55 publications
(101 reference statements)
3
38
0
15
Order By: Relevance
“…Satisfaction refers as an emotional response that follows from cognitive responses to an experience (Smith, 2020;Monferrer et al, 2019;Chong, 2016). Research in the tourism context has already established the association between satisfaction and revisit intention and empirically recognized that satisfaction lays a significant impact on creating a positive revisit intention by tourist (Hasan et al, 2019;Breiby and Slåtten, 2018).…”
Section: Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…Satisfaction refers as an emotional response that follows from cognitive responses to an experience (Smith, 2020;Monferrer et al, 2019;Chong, 2016). Research in the tourism context has already established the association between satisfaction and revisit intention and empirically recognized that satisfaction lays a significant impact on creating a positive revisit intention by tourist (Hasan et al, 2019;Breiby and Slåtten, 2018).…”
Section: Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…The study of mobile service user behavior is a topic of current interest in the scientific marketing community (e.g. Smith, 2020; Calvo-Porral and Otero-Prada, 2020; Calvo-Porral and Nieto-Mengotti, 2019). One of the most interesting related issues is the adoption of mobile payment (Liébana-Cabanillas, et al , 2019).…”
Section: Conceptual Framework and Development Of The Hypothesesmentioning
confidence: 99%
“…Moreover, numerous studies have researched the relationship between self-image, brand personability, and customer satisfaction; where postpurchase behaviors have been the focus of most of these studies (Graeff, 1996;Sirgy, 1982). Similarly, the congruence of self-image on satisfaction has been a topic of debate in many pieces of research, and a significant positive correlation has been reported (Chon, 1990;Jamal & Goode, 2001;Smith, 2020). Brand personality in the financial sector has not been a much-researched area.…”
Section: Brand Personality and Customer Satisfactionmentioning
confidence: 99%